2018
DOI: 10.20546/ijcmas.2018.712.256
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Chilli (Capsicum annuum L.) Genotypes for Yield and Yield Attributing Traits

Abstract: Pradesh (India) to identify potential genotypes for twelve quantitative traits among fifty three genotypes of chilli (Capsicum annuum L.). The analysis of variance revealed significant differences among the genotypes for all the twelve characters indicating the presence of genetic variability among the genotypes. Among fifty three genotypes, the genotype Meghalaya Local recorded maximum plant height, plant spread and number of primary branches per plant. Whereas, the genotype IHR 2900 recorded the earliest for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
5
1
0
Order By: Relevance
“…The analysis of variance (table 2) revealed significant differences among the genotypes for all the 14 characters studied indicating the presence of genetic variability in the genotypes and considerable scope for their improvement. These results are in conformity with earlier reports of Nagaraju et al, (2018), Nahak et al, (2018), Parmajeeth and Akhilesh (2019) in chilli.…”
Section: Resultssupporting
confidence: 94%
See 3 more Smart Citations
“…The analysis of variance (table 2) revealed significant differences among the genotypes for all the 14 characters studied indicating the presence of genetic variability in the genotypes and considerable scope for their improvement. These results are in conformity with earlier reports of Nagaraju et al, (2018), Nahak et al, (2018), Parmajeeth and Akhilesh (2019) in chilli.…”
Section: Resultssupporting
confidence: 94%
“…The characters showing wide range of variation provide ample scope for selecting desired types. These results are in accordance with those reports of earlier workers like Nagaraju et al, (2018), Nahak et al, (2018), Parmajeeth andAkhilesh (2019). The genotypes LCA-49, LCA-51, LCA-39, LCA-23 were identified as promising genotypes due to more number of fruits, ripe yield per plant.…”
Section: Growth Attributessupporting
confidence: 94%
See 2 more Smart Citations
“…Odeleye & Odeleye (2001) reported that cultivars and genetic make-up attribute yield difference. The variation in fresh weight was reported by Srinivas et al, (2017) and Nagaraju et al, (2018) in Chilli genotypes. Difference in number of fruit per plant was statistically different (p<0.001) with HRCCAP-003 having maximum number of fruit per plants followed by HRDCAP-004, but were statistically at par (p>0.05).…”
Section: Figure 1 Fruit Of Capsicum Genotypes Under Studymentioning
confidence: 93%